ALOKASI OPTIMAL UKURAN SAMPEL DATA LONGITUDINAL DUA GRUP DENGAN RESPON KONTINU DAN MATRIKS KOVARIAN COMPOUND SYMMETRY - , CAMELIA FALISA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sample size is the number of individual used in research or experiment. Innacurate sizing of the sample will prevent the sample from representing the population properly. Sample size estimation and optimal allocation must be appropriate with hipothesis of study design. So that longitudinal study which are recuring observation to individu or observation with time. This paper examines optimal allocation for two-groups longitudinal data with continuous response and compound symmetry covariance matrix and provide methods to find the optimal combination of number of participans and number of repeated measures for maximizing power under a fixed budgetary constraint or minimizing budget under fixed power constraint. So the investigator get effective and efficient sample size.